Outcome of blood group system on selfie loving - Muhammad Imran Qadir; Muhammad Hamad Saif (Archives of Hematology Case Reports and Reviews - Peertechz Publications, 2019)
Objective of the present study was co-relating blood groping with selfie lover. A questionnaire was prepared about Selfie lover. Total numbers of students were 169 students in this research and the average age of students was 18-22 years. All the students give answer according to their blood group. Results completed according to project. We took blood sample of every student of Biotechnology. We took three spots on every slide, spot A, B and D mix antigen A, B and D respectively so we indentified blood group of every student.